A comparative study of gastric adenocarcinoma HER2 IHC phenotype and mass spectrometry-based quantification - Xu, Bin; Chen, Hui; Zhang, Jingjing; Cong, Yanghai; Ning, Li; Chen, Limin; Zhang, Yushi; Zhang, Yong; Song, Zhanchun; Meng, Yuan; He, Lianqi; Liao, Wei-li; et al. (Frontiers in Oncology, 2023)
Gastric cancer is a highly heterogeneous malignant tumor of the digestive system. Anti-HER2 treatment can inhibit downstream signaling pathways and improve clinical treatment and outcomes in patients with HER2 protein overexpression. Currently, two standard methods for evaluating HER2 expression status are immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). In this study, we presented a new HER2 protein detection method based on mass spectrometry selected reaction monitoring (MS-SRM), determined the upper and lower limits of HER2 expression detection (300-700 amol/µg), and validated the method. We conducted a retrospective study on 118 formalin-fixed paraffin-embedded (FFPE) tissues from patients with advanced gastric adenocarcinoma in northern China, and we compared the MS-SRM results with those from IHC and correlated them with FISH. The established MS-SRM method can accurately detect the level of HER2 protein expression in tumor cells and has several advantages over IHC. We also found that, among samples with mixed Lauren subtypes, those with a high level of HER2 expression had typical intestinal type features in pathology. We propose that this method can be used as a supplement to IHC.